Solid-State Microwave High-Power Amplifiers. - Sechi, Franco (Artech House, 2009)
This practical resource offers expert guidance on the most critical aspects of microwave power amplifier design. This comprehensive book provides descriptions of all the major active devices, discusses large signal characterization, explains all the key circuit design procedures. Moreover you gain keen insight on the link between design parameters and technological implementation, helping you achieve optimal solutions with the most efficient utilization of available technologies. The book covers a broad range of essential topics, from requirements for high-power amplifiers, device models, phas.